Using a Multiplex Nucleic Acid in situ Hybridization Technique to Determine HCN4 mRNA Expression in the Adult Rodent Brain - Oyrer, Julia; Bleakley, Lauren E.; Richards, Kay L.; Maljevic, Snezana; Phillips, A. Marie; Petrou, Steven; Nowell, Cameron J.; Reid, Christopher A. (Frontiers in Molecular Neuroscience, 2019)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels carry a non-selective cationic conductance, Ih, which is important for modulating neuron excitability. Four genes (HCN1-4) encode HCN channels, with each gene having distinct expression and biophysical profiles. Here we use multiplex nucleic acid in situ hybridization to determine HCN4 mRNA expression within the adult mouse brain. We take advantage of this approach to detect HCN4 mRNA simultaneously with either HCN1 or HCN2 mRNA and markers of excitatory (VGlut-positive) and inhibitory (VGat-positive) neurons, which was not previously reported. We have developed a Fiji-based analysis code that enables quantification of mRNA expression within identified cell bodies. The highest HCN4 mRNA expression was found in the habenula (medial and lateral) and the thalamus. HCN4 mRNA was particularly high in the medial habenula with essentially no co-expression of HCN1 or HCN2 mRNA. An absence of Ih-mediated ‘sag’ in neurons recorded from the medial habenula of knockout mice confirmed that HCN4 channels are the predominant subtype in this region. Analysis in the thalamus revealed HCN4 mRNA in VGlut2-positive excitatory neurons that was always co-expressed with HCN2 mRNA. In contrast, HCN4 mRNA was undetectable in the nucleus reticularis. HCN4 mRNA expression was high in a subset of VGat-positive cells in the globus pallidus external. The majority of these neurons co-expressed HCN2 mRNA while a smaller subset also co-expressed HCN1 mRNA. In the striatum, a small subset of large cells which are likely to be giant cholinergic interneurons co-expressed high levels of HCN4 and HCN2 mRNA. The amygdala, cortex and hippocampus expressed low levels of HCN4 mRNA. This study highlights the heterogeneity of HCN4 mRNA expression in the brain and provides a morphological framework on which to better investigate the functional roles of HCN4 channels.